METABOLIC MYOPATHIES (MMS) - Nesma Fouad Mohammed Ali, Tahia H. Saleem, Tahany A. Abdallah, Omyma A. Hasan, Mohammed H. Hassan (Chelonian Research Foundation, 2025)
Metabolic myopathies are a group of inherited illnesses affecting skeletal muscle metabolism due to enzymatic deficiencies in glycogen breakdown, fatty acid oxidation, or mitochondrial energy production. These disorders result in exercise intolerance, muscle weakness, & rhabdomyolysis (muscle breakdown resulting in the release of toxic cellular components into the bloodstream), which may progress to chronic muscle degeneration and functional impairment. Diagnosis relies on clinical symptoms, biochemical markers, genetic testing, and muscle biopsy. Common disorders include glycogen storage diseases like McArdle illness, which impairs glycogen breakdown, fatty a` oxidation disorders like carnitine palmitoyl transferase II deficiency that disrupts lipid metabolism, and mitochondrial myopathies, which affect cellular energy production. Management strategies focus on dietary modifications, including tailored carbohydrate or fat intake, controlled exercise programs to prevent muscle damage, and novel therapies like enzyme replacement treatment and gene therapy. Supportive treatments, including symptom management and physical therapy, also play a crucial role in improving mobility & overall well-being. Early diagnosis and individualized interventions are essential for optimizing patient outcomes, minimizing complications, and enhancing quality of life. Continued research into the molecular mechanisms of these disorders is vital for developing more effective therapies and improving long-term prognosis.